Introducing Aviary - Peutz, Mike (2009 Springer E-Books., 2009)
The world is changing. Where before you needed to purchase and install big and expensive programs on your computer in order to create stunning images, you can now do it all online for free using Aviary. Aviary is an online collection of applications that enable you to upload and modify your own photographs and images, and create new imagery from scratch. It includes a powerful photo-manipulation tool called Phoenix, a vector-drawing application called Raven, an effects suite for creating eye-watering image effects called Peacock, and much more. Introducing Aviary takes you through all of these tools, showing you how to use each tool individually and also how to combine the tools across the suite to create some truly stunning artwork.